Chloride intercellular channel 3 suppression‐mediated macrophage polarization: a potential indicator of poor prognosis of hepatitis B virus‐related acute‐on‐chronic liver failure. Issue 5 (13th April 2022) - Liang, Jing; Long, Zijie; Zhang, Yanyan; Wang, Jundan; Chen, Xiaotong; Liu, Xiangfu; Gu, Yurong; Zhang, Wanling; Zhang, Tong; Chen, Youming; Zhang, Genglin; Sun, Weijun; et al.
Abstract: Patients with hepatitis B virus‐related acute‐on‐chronic liver failure (HBV‐ACLF) are characterized by immune paralysis and susceptibility to infections. Macrophages are important mediators of immune responses can be subclassified into two main phenotypes: classically activated and alternatively activated. However, few studies have investigated changes to macrophage polarization in HBV‐related liver diseases. Therefore, we investigated the functional status of monocyte‐derived macrophages (MDMs) from patients with mild chronic hepatitis B ( n = 226), HBV‐related compensated cirrhosis ( n = 36), HBV‐related decompensated cirrhosis ( n = 40), HBV‐ACLF ( n = 62) and healthy controls ( n = 10), as well as Kupffer cells (KCs) from patients with HBV‐ACLF ( n = 3). We found that during the progression of HBV‐related liver diseases, the percentage of CD163 + CD206 + macrophages increased, while the percentage of CD80 + human leukocyte antigen‐DR + macrophages decreased significantly. MDMs and KCs mainly exhibited high CD163 + CD206 + expression in patients with HBV‐ACLF, which predicted poor clinical outcome and higher liver transplantation rate. Transcriptome sequencing analysis revealed that chloride intracellular channel‐3 (CLIC3) was reduced in patients with HBV‐ACLF, indicating a poor prognosis. To further study the effect of CLIC3 on macrophage polarization, human monocytic THP‐1 cell‐derived macrophages were used. We found that classical and alternative macrophage activation occurred through nuclear factor kappa B (NF‐κB) and phosphoinositide 3‐kinase/protein kinase B pathways, respectively. CLIC3 suppression inhibited NF‐κB activation and promoted the alternative activation. In conclusion, macrophage polarization gradually changed from classically activated to alternatively activated as HBV‐related liver diseases progressed. Both CLIC3 suppression and increased alternatively activated macrophage percentage were potential indicators of the poor prognosis of patients with HBV‐ACLF. Abstract : In this work, our results reveal that macrophage polarization gradually changes from classically activated to alternatively activated as hepatitis B virus (HBV)‐related liver diseases progress. In patients with HBV‐related acute‐on‐chronic liver failure (HBV‐ACLF), macrophages mainly display alternatively activated features. We also identify a previously undescribed role for chloride intercellular channel 3 (CLIC3) in macrophage polarization. CLIC3 regulates macrophage polarization through nuclear factor kappa B and phosphoinositide 3‐kinase/protein kinase B signaling pathways. Both CLIC3 suppression and increased alternatively activated macrophage percentage are the potential indicators of the poor prognosis of patients with HBV‐ACLF.